Prarancangan Pabrik Asam Oksalat Dihidrat dari Molasses dan Asam Nitrat dengan Kapasitas 15.000 Ton/Tahun - Sara, Efany; , Dr. Ir. Ahmad M. Fuadi, M.T; , Emi Erawati S.T., M. Eng (2016)
The manufacture of oxalic acid dihydrate from molasses and nitric acid with a capacity of 15,000 ton/year was planned to be established in 2020 in the Industry Area of Gresik, East Java. The manufacturer was planned to be established to operate continuously for 330 days per year with an amount of employees as many as 115 people. In Indonesia itself, there is no manufacturer of oxalic acid, therefore, if the manufacturer oxalic acid is established, it will fulfill the domestic needs and will reduce the import of oxalic acid product from foreign countries. The stages of making oxalic acid through an oxidation process of nitric acid is begun with the preparation of the raw material of molasses as much as 1861.134 kg/hours and nitric acid as much as 3400.95 kg/hours, continued with the stage of reaction of forming oxalic acid, the stage of crystallization, and the stage of drying the product. The reaction of forming oxalic acid is helped by catalysts H2SO4 and V2O5 as much as 646.21 kg/hours and 0.063 kg/hours using the reactor of Continuous Stirred Tank Reactor (CSTR). The reaction takes place in the phase of liquid-liquid, reversible, exothermic, and non isothermal at temperature of 71oC and pressure of 1 atm. To support the process of production, the supporting unit of process or utilities is needed to establish comprising a unit of water supply as much as 68,428.286 kg/hours, the electricity needed is as much as 567.338 kW, the compressed air is as much as 150 m3/hours, and the needs of fuel as much as 367,775 liters/hours as well as laboratory. From the economic analysis conducted to this manufacturer with a fixed capital as much as IDR 24,765,546,310 and the working capital as much as IDR 30,945,467,632, it obtains Return of Investment (ROI) before tax as much as 33.7% and after tax as much as 25.3%. Meanwhile, Pay Out Time (POT) before and after tax are 2,29 years and 2,83 years. Break Event Point and Shut Down Point are as much as 40,8% and 21,5%. For Internal Rate of Return based on DCF is counted as much as 38%. Based on the calculation of the economic analysis, it can be concluded that this manufacturer is reasonable to establish.